Commuting demands and appraisals: A systematic review and meta-analysis of strain and wellbeing outcomes. (February 2023) - Murphy, Lauren D.; Cobb, Haley R.; Rudolph, Cort W.; Zacher, Hannes
Research on commuting to work and its potential consequences for employee strain and wellbeing has accumulated across various disciplines. However, this has led to a narrow research scope with wide methodological variability. An integration of this literature is needed to understand the breadth of the commuting experience and interpret heterogeneous findings. Extending the transactional stress model, we propose that commuting is a demand that can have both negative and positive effects on outcomes through commuting appraisals. We present a systematic review (k = 109 studies) and meta-analysis (k = 39 studies) of these relationships. Our systematic review finds partial support for our hypotheses, and our meta-analysis suggests that objective commuting demands are positively associated with strain outcomes (r ̅_xy = .089; especially perceived stress, r ̅_xy = .153), but unrelated to wellbeing outcomes. Subjective commuting appraisals are unrelated to strain or wellbeing outcomes. We conclude with recommendations for methodological improvements and implications for research and practice. Plain language summary: Commuting is a nearly ubiquitous part of contemporary employment. Over the last several decades, empirical research on commuting has accumulated across various disciplines. Our systematic review and meta-analysis take stock of relationships regarding commuting demands, appraisals of commuting, and strainand wellbeing-related outcomes. The results of the qualitative review indicate that there are both positive and negative implications of commuting. Commuting demands are related to favorable and unfavorable appraisals, and commuting demands are also related to both strain and wellbeing outcomes. However, the result of our quantitative meta-analysis suggests that time spent commuting is positively associated with strain outcomes, but unrelated to wellbeing outcomes. Subjective commuting appraisals are unrelated to strain and wellbeing outcomes. We outline implications for future research (e.g., commuting's role in boundary management), highlight methodological challenges (e.g., variability in reporting), and provide recommendations for practice (e.g., offer resources that mitigate consequences of commuting).